Analisis Stilistika dalam Lagu Jawa Widodari Karya Denny Caknan - Wulandari, Arum; Alfiah, Alfiah (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
The song Widodari is a song that uses the dangdut genre and is sung by Denny Caknan using the Javanese language. An interesting thing to study further is the use of diction, namely by looking at the style of language used. The purpose of this study was to analyze the diction contained in the lyrics of the song Denny Caknan. Stylistic studies are directed to discuss the content of literary works. In general, regulating stylistic studies includes diction or word choice (lexical choice), sentence structure, figure of speech, partnership, rhyme patterns, and dimensions used for authors or available in literary works. This study aims to analyze the use of diction and themes contained in Denny Caknan's Dangdut Song Lyrics. The method used is a qualitative descriptive method because the object is the text of the Song Lyrics. Data was taken from 1 album by random sampling and was considered representative. The theory used in this research is stylistic. The stylistic theory is used to see aesthetic beauty in song lyrics. The end of this research is the result of the data analysis presentation. The presentation of the results of the data analysis begins with the presentation of the diction on the data source contained in the lyrics of the song Denny Caknan. Then proceed with an explanation of the theme of the lyrics. The results of the research found are diction and themes in the Widodari song which was popularized by Denny Caknan.